Laser ion source for high brightness heavy ion beam. (5th September 2016) - Okamura, M.
Abstract: A laser ion source is known as a high current high charge state heavy ion source. However we place great emphasis on the capability to realize a high brightness ion source. A laser ion source has a pinpoint small volume where materials are ionized and can achieve quite uniform low temperature ion beam. Those features may enable us to realize very small emittance beams. In 2014, a low charge state high brightness laser ion source was successfully commissioned in Brookhaven National Laboratory. Now most of all the solid based heavy ions are being provided from the laser ion source for regular operation.